Earthquake [videorecording] - Fox, George; Lang, Jennings; Puzo, Mario; Robson, Mark (A Mark Robson Filmmakers Group Production [producer], 1975)
A story of the most catastrophic earthquake in Southern California sending shockwaves through the lives of the people there. Charlton Heston, a rugged engineer who lives with his spoiled and wealthy wife Ava Gardner, George Kennedy, a tough cop in a city of devastation and Lome Green, a construction owner trapped in his own building are the major casts.